A mid-circuit erasure check on a dual-rail cavity qubit using the joint-photon number-splitting regime of circuit QED - Stijn J. de Graaf; Sophia H. Xue; Benjamin J. Chapman; James D. Teoh; Takahiro Tsunoda; Patrick Winkel; John W. O. Garmon; Kathleen M. Chang; Luigi Frunzio; Shruti Puri; Robert J. Schoelkopf (npj Quantum Information)
Abstract Quantum control of a linear oscillator using a static dispersive coupling to a nonlinear ancilla underpins a wide variety of experiments in circuit QED. Extending this control to more than one oscillator while minimizing the required connectivity to the ancilla would enable hardware-efficient multi-mode entanglement and measurements. We show that the spectrum of an ancilla statically coupled to a single mode can be made to depend on the joint photon number in two modes by applying a strong parametric beamsplitter coupling between them. This ‘joint-photon number-splitting’ regime extends single-oscillator techniques to two-oscillator control, which we use to realize a hardware-efficient erasure check for a dual-rail qubit encoded in two superconducting cavities. This scheme leverages the high-fidelity beamsplitter coupling already required for single- and two-qubit gates while permitting minimal crosstalk between circuit elements. Furthermore, the flexibility to choose the pulse shape allows us to limit the susceptibility to different error channels. We use this scheme to detect leakage errors with a missed erasure fraction of (9.0 ± 0.5) × 10−4 while incurring an erasure rate of 2.92 ± 0.01% and a Pauli error rate of 0.31 ± 0.01%, both of which are dominated by cavity errors.